Argumentação e multimodalidade: análise dos processos referenciais em textos da rede social X - Almeida, Eduardo Carvalho de (2023)
This research has the goal of analyze, through referential processes(Cavalcante; Custódio Filho; Brito, 2014; Cavalcante; Brito, 2016; among others), how visual resources are mobilized as argumentative strategies in verbal and visual texts. To execute this investigation, the study adopts the presumed theory and methodology from Text Linguistics (TL), which has the text and the textual strategies as its object of study, defined by Cavalcante et al. (2019) as a unity of communication and meaning in context,composed by different semiotic systems. Apart from that, TL, inspired by research from Ruth Amossy about argumentation and discourse, admits that every text is argumentative (Cavalcante et al., 2020). It is supposed that images present in verbal and visual texts are also part of argumentative strategies. To investigate them, Social Semiotics (Kress, 2010; Kress; Van Leeuwen, 2021) was chosen to provide an analytical apparatus which contributed to the description of argumentative strategies underlying the selected texts. The corpus consists of 24 posts with verbal and visual journalistic headlines, published by verified profiles by X social media on the covid-19 theme. The analysis of the texts was made in three steps: reconstruction of argumentative reasoning (enthymemes) based on the central topics of the texts; description of referential processes of introduction and anaphor (Cavalcante; Brito, 2016); and identification of visual resources according to the Grammar of Visual Design (Kress; Van Leeuwen, 2021). It was possible to verify, after the analysis, that it was the role of the images on the description of the discursive topic that made the reconstruction of implied opinions possible and that their role toke part not only on premises or conclusions of the arguments, but on its global understanding, via referential nets. It was noticed that the most cotextual elements were related to the minor explicit premises, and these elements were textual clues to get to major premises and implicit conclusions.